Letters of George Ade - Tobin, Terence (Purdue University Press, 2019)
George Ade, one of the most beloved writers of his day, carried on a lively correspondence with the most colorful of great and near-great. George M. Cohan, William Howard Taft, Theodore Roosevelt, John T. McCutcheon, James Whitcomb Riley, Finley Peter Dunne, Hamlin Garland all received letters from the Hoosier humorist. Ade's keen observation, compact and straight-forward style, and understated humor mark his correspondence as well as his immensely popular newspaper columns, books, and plays. As Paul Fatout writes in his foreword: "The charm of George Ade lies in his good-natured contemplation of our species, which delineates, not with malice or with condescension, but with the gusty enjoyment of a spectator entertained by a continuous variety show." Ade traveled the world over many times, but always returned to the home he never really left-Indiana. His companions and correspondents included presidents, senators, Hollywood moguls, and Broadway stars, but his first allegiance was to the farmlands and small towns of mid-America. From Hazelden Farm, near Brook, he kept in close touch with politicians from the precincts to the governor's mansion. He wrote to educators, editors, and executives, and took an active part in the life and growth of his alma mater, Purdue University. Characteristically, the man who succeeded as a writer by setting down familiar situations sent some of his most interesting letters to ordinary citizens all over the state. Ade's friendships were so diversified that his correspondence forms a patchwork of popular history, literature, politics, and entertainment. His interchange of ideas about people and events shaping the twentieth century as well as his own life will provide insights for students of varied aspects of American culture. This volume presents 182 of the most interesting and informative letters from the thousands of extant pieces of his correspondence in scores of collections scattered throughout the United States. The letters are arranged chronologically annotated with explanatory material and with sources. A foreword, introduction and Ade's biography are included. Photographs, sketches, handwriting samples, and other illustrations which evoke the man and his times are interspersed with the text.